Loss of the Ability to Control Right-to-Left Shunt Does Not Influence the Metabolic Responses to Temperature Change or Long-Term Fasting in the South American Rattlesnake Crotalus durissus - Leite, Cleo A. C.; Wang, Tobias; Taylor, Edwin W. [UNESP]; Abe, Augusto S. [UNESP]; Leite, Gabrielle S. P. C.; Andrade, Denis O. V. de [UNESP] (Univ Chicago Press, 2014)
In the undivided ventricle of noncrocodilian reptiles, the blood perfusing the systemic circulation is a controlled combination of oxygenated pulmonary blood, flowing from left to right across the heart, and relatively deoxygenated systemic blood, flowing from right to left. A clear inverse correlation has been experimentally established between metabolic demand and the magnitude of right-to-left cardiac shunt in several reptile groups. Unilateral left vagotomy renders the single effective pulmonary artery of the South American rattlesnake (Crotalus durissus) unable to adjust the magnitude of blood flow to the lung. This provides a unique model for investigation of the long-term consequences of abolition of the cardiac shunt in a squamate reptile. Rattlesnakes-vagotomized on the left or right side or sham operated-were exposed to long-term food deprivation or temperature change. Loss of control of the cardiac shunt following selective vagotomy did not change the progressive decrease in body mass or the onset of identifiable fasting stages. Resting metabolic rate and the increase in oxygen uptake measured during spontaneous or forced activity were also unchanged. The responses to reductions in temperature (from 30 degrees to 20 degrees or 15 degrees C) in adult snakes or juvenile snakes were similarly unaffected by vagal transection. These data support rejection of the hypothesis that adjustment of the cardiac shunt is central to the control metabolic rate in squamate reptiles.